Evaluation of fluoride levels in bottled water and their contribution to health and teeth problems in the United Arab Emirates - Mohamed Yehia Z. Abouleish (Elsevier, 2016)
Fluoride is needed for better health, yet if ingested at higher levels it may lead to health problems. Fluoride can be obtained from different sources, with drinking water being a major contributor. In the United Arab Emirates (UAE), bottled water is the major source for drinking. The aim of this research is to measure fluoride levels in different bottled water brands sold in UAE, to determine whether fluoride contributes to better health or health problems. The results were compared to international and local standards. Fluoride was present in seven out of 23 brands. One brand exhibited high fluoride levels, which exceeded all standards, suggesting it may pose health problems. Other brands were either below or above standards, suggesting either contribution to better health or health problems, depending on ingested amount. A risk assessment suggested a potential for non-cancer effects from some brands. The results were compared to fluoride levels in bottled water sold in UAE and neighboring countries (e.g. Saudi Arabia, Qatar, Kuwait, and Bahrain), over 24 years, to reflect on changes in fluoride levels in bottled water in this region. The research presents the need for creating, stricter regulations that require careful fluoride monitoring and new regulations that require listing fluoride level on the bottled water label, internationally and regionally. The research will have local and global health impact, as bottled water sold in UAE and neighboring countries, is produced locally and imported from international countries, e.g. Switzerland, the USA, France, Italy, New Zealand, and Fiji. Keywords: Fluoride, Bottled water, Teeth health, United Arab Emirates